Degradable magnesium alloy
The magnesium alloy with controlled Al, Cu, and Mn content and finely dispersed intermetallic compounds addresses the challenge of adjusting corrosion rates in fracking applications, achieving high productivity and effective removal of fracking members.
Patent Information
- Application Number
- JP2021552468
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-16
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing degradable magnesium alloys for fracking applications lack control over the distribution and size of intermetallic compounds, which affects the corrosion rate and tensile strength, limiting their ability to adjust corrosion rates according to site-specific conditions.
A magnesium alloy with a composition of 7.0% to 13.0% Al, 4.5% to 13.0% Cu, and less than 0.10% Mn, featuring finely dispersed intermetallic compounds, which allows for individual adjustment of corrosion rate and tensile strength by controlling the amount and distribution of Cu-Al-Mg intermetallic compounds.
The magnesium alloy achieves a high and adjustable corrosion rate while maintaining sufficient tensile strength, enhancing mining productivity by allowing for timely removal of fracking members.
Smart Images

Figure 0007671252000005 
Figure 0007671252000006 
Figure 0007671252000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a degradable magnesium alloy that can be tailored to any corrosion rate. [Background technology]
[0002] Shale oil and gas are extracted using a technique known as hydraulic fracturing (fracking). In this technique, wells are drilled to rock formations that contain oil or gas, and these rocks are fractured using hydraulic pressure, after which the oil or gas is released and recovered. This fracturing and recovery process is carried out multiple times within the well. Therefore, in order to increase the productivity of fracking, it is necessary to quickly remove the materials used in the previous fracking and shorten the time until the next fracking.
[0003] Methods for quickly removing the fracking members include drilling through the fracking members, and dissolving the fracking members by corrosion. The latter method is more productive, but requires that the materials that make up the fracking members retain sufficient mechanical properties to function as fracking members while corroding quickly thereafter.
[0004] Materials used for such fracking components include highly degradable polymer materials and magnesium alloys. Magnesium alloys are particularly suitable when high tensile strength is required. If the material itself corrodes quickly, mining productivity will naturally improve. In addition, by improving the mechanical strength of the material, it is possible to achieve the function with thinner components, which will result in a shorter time required for decomposition, leading to improved mining productivity.
[0005] Furthermore, such degradable magnesium alloys are sometimes used together with degradable polymeric materials, and may be required to have degradability and strength that match the degradable polymeric materials.
[0006] As a specific example of decomposability, Non-Patent Document 1 states that the typical corrosion rate of a decomposable frac plug is 1000 to 1500 mg / cm in a 2% KCl solution. 2 It is mentioned that it is / day.
[0007] Patent Document 1 describes a decomposable Mg alloy that contains 3.9 mass% or more and 14.0 mass% or less of Al, 0.1 mass% or more and 0.6 mass% or less of Mn, 0.01 mass% or more and 10.0 mass% or less of Ni, Cu, or both, and the balance being Mg and unavoidable impurities.
[0008] Patent Document 2 describes a highly corrosive magnesium alloy for extrusion materials, which contains a total of 0.02 to 5% (by weight, the same applies below) of one or more of Ni, Fe, and Cu, 0.5 to 3.5% Al, 0.2 to 1.5% Zn, and the balance being Mg and unavoidable impurities.
[0009] Furthermore, Patent Document 3 describes a corrosive magnesium alloy containing, by mass, 1-6% Al, 1-6% Zn, 1-3% Fe, 5-15% Cu, 0.1-1% Ag, and 0.1-1.2% Ni.
[0010] Moreover, Patent Document 4 describes a decomposable magnesium alloy containing, by mass ratio, 3.0 to 12% Al, 0.5 to 5% Zn, 0.5 to 3% Cu, and 0.1 to 1.0% Na.
[0011] Patent Document 5 describes a decomposable magnesium alloy containing, by mass, 3-15% Al, 0.5-5% Zn, 0-5% Cu, and 0-5% Ni, where the Cu and Ni are not both 0 at the same time. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] WO2017168696A1 [Patent Document 2] Japanese Patent Application Publication No. 02-232332 [Patent Document 3] CN104498792A [Patent Document 4] CN107523732A [Patent Document 5] CN107587019A [Non-patent literature]
[0013] [Non-Patent Document 1] “Degradation Study on Materials for Dissolvable FracPlugs”, S. Takahashi et al., Unconventional Resources Technology Conference (URTeC),2901283, DOI 10.15530 / urtec 2018 2901283 Summary of the Invention [Problem to be solved by the invention]
[0014] As shown in these documents, corrodible or decomposable magnesium alloys are often designed to increase the corrosion rate by forming a compound phase containing a metal phase or intermetallic compound more noble than Mg in the Mg matrix by adding a metal element such as Cu or Ni that is more noble in potential than Mg, and by microcell corrosion between the intermetallic compound and Mg. Increasing the amount of addition of a metal element such as Cu or Ni that is more noble in potential than Mg increases the corrosion rate, but there is no prior art that discloses the effect of the distribution of intermetallic compounds that is generated in this case on the corrosion rate.
[0015] Therefore, the object of this invention is to obtain a magnesium alloy in which the corrosion rate and tensile strength can be individually adjusted by controlling the amount of intermetallic compounds produced, as well as their size and distribution, thereby enabling the corrosion rate to be appropriately adjusted according to on-site conditions, thereby further improving mining productivity. [Means for solving the problem]
[0016] The present invention solves the above problem by providing a magnesium alloy containing 7.0% by mass or more and 13.0% by mass or less of Al, 4.5% by mass or more and 13.0% by mass or less of Cu, 0% by mass or more and less than 0.10% by mass of Mn, and the remainder being Mg and unavoidable impurities, and having finely dispersed intermetallic compounds. The corrosion rate and tensile strength of a decomposable structural member made of this magnesium alloy can be individually adjusted.
[0017] Regarding each component, specifically, the addition of Al mainly increases the tensile strength. Also, the addition of Cu generates Cu-Al-Mg intermetallic compounds with a noble potential, and the potential difference between α-Mg and Cu-Al-Mg intermetallic compounds can promote the loss of α-Mg due to microcell corrosion, mainly increasing the decomposition rate. Magnesium alloys have a problem that the tensile strength decreases when the Cu content is increased, as the Cu-Al-Mg intermetallic compounds increase or become coarse. However, if the amount and distribution of Cu-Al-Mg intermetallic compounds are controlled and their size is refined to improve their dispersibility, the corrosion rate can be increased without decreasing the tensile strength.
[0018] As a method for refining and dispersing the intermetallic compounds, it is possible to select a method for applying a large strain to the cast material after casting. Specific examples of processing methods that apply a large strain include drawing, extrusion, rolling, pressing, and Equal Channel Angular Pressing (ECAP). By applying strain, the intermetallic compounds are refined and reduced in size, and the fine intermetallic compounds are dispersed, reducing the number of large lumps, changing the distribution and improving dispersibility.
[0019] That is, in the magnesium alloy according to the present invention, the corrosion rate and tensile strength can be adjusted to presumably suitable values by adjusting the amounts of Al and Cu contained therein and the size and distribution of the intermetallic compounds. Effect of the Invention
[0020] Degradable structural components made from the magnesium alloy of the present invention can be used during fracking and can be degraded at a rate appropriate for the site, increasing mining productivity. [Brief description of the drawings]
[0021] [Figure 1] SEM image showing the composition of the cast material of Example 5 [Diagram 2] Figure 1: EDS analysis results of intermetallic compounds observed in bright field [Diagram 3] XRD spectrum of the cast material of Example 5 [Figure 4] SEM image showing the composition of the processed material in Example 5 [Diagram 5] SEM image showing the composition of the cast material of Example 3 [Figure 6] SEM image showing the composition of the cast material of Example 1 [Figure 7] SEM image showing the composition of the cast material of Comparative Example 1 [Figure 8] SEM image showing the composition of the processed material in Comparative Example 1 [Figure 9] EPMA analysis results of the hexagonal intermetallic compound of Comparative Example 1 [Figure 10] SEM image showing the composition of the cast material of Comparative Example 3 [Figure 11] SEM image showing the composition of the processed material of Comparative Example 3 [Figure 12] Graph showing linear relationship of corrosion rate parameter Pc in Examples and Comparative Examples [Figure 13] Graph showing the ratio of actual corrosion rate to estimated corrosion rate versus Mn content in the examples and comparative examples. [Figure 14] A graph plotting the ratio of actual corrosion rate to estimated corrosion rate versus Cu content in the examples and comparative examples. [Figure 15] Graph showing linear relationship of tensile strength parameter Ps in the examples DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below. The present invention relates to a magnesium alloy that can undergo rapid corrosion under a specified environment, a degradable structural member using the same, and a method for adjusting the corrosion rate in the degradable structural member.
[0023] The Al content of the magnesium alloy according to the present invention must be 7.0% by mass or more. If the Al content is too low, the fluidity during casting will decrease and the amount of Cu-Al-Mg intermetallic compounds will be insufficient, but if the Al content is 7.0% by mass or more, sufficient fluidity and the amount of Cu-Al-Mg intermetallic compounds can be ensured. On the other hand, the Al content must be 13.0% by mass or less. If the Al content is too high, the amount of Cu-Al-Mg intermetallic compounds will be excessive, and if it exceeds 13.0% by mass, the Cu-Al-Mg intermetallic compounds will hinder the progress of Mg corrosion, causing a rapid decrease in the corrosion rate.
[0024] The magnesium alloy according to the present invention may contain Mn. Mn has the effect of removing some elements contained as impurities, and even a small amount of Mn contained therein suppresses the influence of other elements on the corrosion rate to be adjusted, thereby improving the adjustment accuracy of the corrosion rate of a decomposable structural member manufactured from the magnesium alloy. However, the Mn content must be less than 0.10 mass%. This is because, when the Mn content increases, Mn is contained in the Cu-Al-Mg intermetallic compound, which tends to coarsen. When the Cu-Al-Mg intermetallic compound becomes coarse, the corrosion rate decreases.
[0025] The Cu content of the magnesium alloy according to the present invention must be 4.5% by mass or more. By adding Cu, a Cu-Al-Mg intermetallic compound having a noble potential is generated in the structural member obtained by casting the magnesium alloy according to the present invention. The potential difference between α-Mg and the Cu-Al-Mg intermetallic compound promotes the depletion of α-Mg due to microcell corrosion, and the corrosion rate can be improved. In a normal Mg alloy, the corrosion rate tends to decrease when the above-mentioned Al is contained, but if the Cu content is 4.5% by mass or more, the above-mentioned decomposable structural member can achieve a practical corrosion rate even in the above-mentioned range of the Al content. In particular, the Cu content is preferably 7.0% by mass or more. If the Cu content is 7.0% by mass or more, the amount of Cu-Al-Mg intermetallic compounds increases, and when strain is applied to a decomposable structural member obtained by casting this magnesium alloy, it is considered that the Cu-Al-Mg intermetallic compounds are easily broken, which makes the Cu-Al-Mg intermetallic compound phase finer and makes it easier to improve the corrosion rate. On the other hand, the Cu content must be 13.0% by mass or less. If the Cu content exceeds 13.0% by mass, coarse block-shaped Cu-Al-Mg intermetallic compounds are generated during casting, which impedes the progress of Mg corrosion and reduces the effect of improving the corrosion rate due to microcell corrosion caused by adding Cu.
[0026] The magnesium alloy according to the present invention may contain elements other than the above-mentioned elements as inevitable impurities. These inevitable impurities are those that are unavoidably contained against the intention due to manufacturing problems or raw material problems. Examples include elements such as Ag, Fe, Ca, Cd, Ga, In, Li, Mm (misch metal), Ni, Pb, Se, Si, Ti, Y, Zn, and Zr. The content must be within a range that does not impair the properties of the magnesium alloy according to the present invention, and each element is preferably less than 0.2 mass%, and more preferably less than 0.1 mass%. Among these, the content of each of Si, Li, In, and Ca is preferably less than 0.1 mass%, and more preferably less than 0.05 mass%. The less the inevitable impurity elements are, the more preferable they are, since this eliminates uncertain factors that should be considered when adjusting the decomposition rate by Cu, and it is particularly preferable that they are below the detection limit.
[0027] The decomposable structural member manufactured from the magnesium alloy according to the present invention is made up of Mg apart from the above-mentioned Al, Mn, Cu and unavoidable impurities, and is processed so as to have finely dispersed intermetallic compounds.
[0028] The magnesium alloy of the present invention can be prepared by a general method using raw materials containing the above elements so that the composition ratio falls within the above-mentioned mass% range and the decomposition rate is desired. Note that the above mass% does not refer to the raw materials, but to the prepared alloy or the decomposable structural member produced from the alloy by casting, sintering, or the like.
[0029] The preferred degradable structural components of the present invention can be obtained by casting, and by preferred, we mean that they have corrosion rates and tensile strengths that are tailored to suit the conditions of the fracking site and that have properties that improve mining productivity.
[0030] In addition, by subjecting the decomposable structural member obtained by casting to a process that imparts a large strain, the Cu-Al-Mg intermetallic compounds can be finely dispersed, and the corrosion rate and mechanical properties can be improved. Specifically, by imparting strain, the average equivalent diameter d of the Cu-Al-Mg intermetallic compounds can be made smaller. In principle, the smaller the average equivalent diameter d, the better. Specifically, the average equivalent diameter d is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 2 μm or less. On the other hand, it is practically difficult to achieve a diameter less than 0.1 μm, and 0.1 μm or more is realistic, with 0.5 μm or more being a more easily achievable value.
[0031] Methods for applying strain include drawing, extrusion, rolling, pressing, and ECAP (Equal Channel Angular Pressing) to the cast member. These methods can be selected appropriately depending on the shape of the member to be obtained. When a magnesium alloy is cast, the crystal size of α-Mg is 100 to 200 μm in terms of average crystal grain size D, but it is preferable to refine the crystal size to about 5 μm to 25 μm by the above-mentioned extrusion, rolling, drawing, etc.
[0032] The corrosion rate of the decomposable structural component of this invention can be adjusted by the Cu content "CU" and the Al content "AL". It has been found that the tendency can be adjusted according to the square of "CU" and the square of "1 / AL". It can also be adjusted by the average equivalent diameter d of the Cu-Al-Mg intermetallic compounds. The following formula (1) holds for these values and the constant p. Here, Pc is the corrosion rate W Est These parameters are linear functions of the following equation (2) (a1 and b1 are constants that differ for each system). Therefore, the corrosion rate W can be adjusted by adjusting the average equivalent diameter d. Est is adjustable.
[0033] Pc=(CU 2 / AL 2 ) / (1+p×d) (1) W Est = a1 × Pc + b1 (2)
[0034] It was also found that the tensile strength of the disassembly structural member of the present invention can be adjusted according to the first power of "AL" and the first power of "CU". It was also found that it can be adjusted according to the square root of the above-mentioned average equivalent diameter d. The relationship between these values and the constants u and v is given by the following formula (3). Here, Ps is the estimated tensile strength σ T,Est is a parameter that is a linear function of the following formula (4) (a2 and b2 are constants that differ for each system). Therefore, by adjusting the average equivalent diameter d, the tensile strength σ T,Est is adjustable.
[0035] Ps = u × AL-CU + v / (d) 1 / 2 (3) σ T,Est = a2 × Ps + b2 (4)
[0036] By using the above formulas (1) to (4), it is possible to prepare a degradable magnesium alloy structural member having any tensile strength and corrosion rate from the Al content, Cu content, and average equivalent diameter d. Moreover, it is understood from these formulas that the corrosion rate and tensile strength are not necessarily contradictory in the magnesium alloy according to the present invention. Therefore, in the above ranges of the Al, Cu, and Mn contents, the corrosion rate and tensile strength of the highly degradable magnesium alloy can be individually controlled by adjusting the Al content, Cu content, and average equivalent diameter d of the Cu-Al-Mg intermetallic compound based on the relationship between these parameters Pc and Ps and the corrosion rate and tensile strength.
[0037] Examples of products to which the degradable structural members made of magnesium alloy according to the present invention can be applied include drilling tools for oil wells, natural gas wells, etc. Since these are introduced deep underground and exposed to high water pressure, they need to be strong enough to withstand the high pressure environment. On the other hand, when they are no longer needed, they can be removed by being corroded and decomposed at the appropriate time by being exposed to the aqueous solution introduced during the drilling work, without the trouble of removing them from deep underground. EXAMPLES
[0038] The magnesium alloy according to the present invention was actually prepared and components were fabricated. The procedure and test method will be explained below.
[0039] <Sample preparation> Magnesium alloys were prepared so that the content of elements other than Mg was the mass% shown in Table 1 below, and then heated to 700°C and cast into an iron mold to produce cast materials. Next, an external force was applied to the cast materials heated to approximately 370°C, giving them a strain of 560%, producing processed materials. As a result of this processing, the cross-sectional area of the processed materials was reduced to 1 / 32 of that of the cast materials.
[0040] [Table 1]
[0041] FIG. 1 is a composition image obtained by SEM observation of the cast material of Example 5. FIG. 2 is an EDS analysis result of the intermetallic compounds observed in the bright field of FIG. 1. FIG. 3 is an XRD result of the cast material of Example 5. From these results, it is clear that the cast material contains α-Mg, Cu-Al-Mg intermetallic compounds, Mg 17 Al 12 It can be seen that the cast material is composed of α-Mg, Cu-Al-Mg intermetallic compounds, and Mg. Figure 4 shows a composition image obtained by SEM observation of the processed material of Example 5. It can be seen that the Cu-Al-Mg intermetallic compounds are broken down and crushed by processing and are finely dispersed. From these facts, namely, (1) "The cast material is composed of α-Mg, Cu-Al-Mg intermetallic compounds, Mg 17 Al 12 The same applies to the other examples and comparative examples.
[0042] The average equivalent diameter d of Cu-Al-Mg intermetallic compounds in Table 1 is the result of measuring the average equivalent diameter d (μm) of Cu-Al-Mg intermetallic compounds by identifying bright field areas by image analysis of composition images obtained by SEM observation of processed materials, and calculating the arithmetic average of the average equivalent diameter d (μm). The average grain size D of α-Mg is the result of measuring the average grain size D of α-Mg by identifying grain boundaries by image analysis of images obtained by optical microscope observation after grain boundary corrosion of processed materials. Here, the arithmetic average of the average equivalent diameter d and the average grain size D is the value obtained by dividing the total of the measured grain sizes by the number of measured particles. In the examples and comparative examples, the sizes of Cu-Al-Mg intermetallic compounds are various, but the grain sizes are not significantly different.
[0043] 5 and 6 are composition images obtained by SEM observation of the cast materials of Example 3 and Example 1. With regard to the Cu-Al-Mg intermetallic compounds, Example 3, which has a low Cu content, has a mesh-like shape over the entire surface, whereas Example 1, which has a high Cu content, has a loose shape. That is, when the Cu content is less than 7.0 mass%, the Cu-Al-Mg intermetallic compounds become mesh-like, and when strain is applied, the stress distribution becomes uniform, and the Cu-Al-Mg intermetallic compounds are not easily crushed, whereas when the Cu content is 7.0 mass% or more, the Cu-Al-Mg intermetallic compounds become loose, and therefore stress concentration is likely to occur when strain is applied, and it is considered that this indicates that even with a relatively small applied strain, the Cu-Al-Mg intermetallic compounds are easily crushed and refined, and the dispersibility is likely to be increased.
[0044] 7 and 8 are composition images obtained by SEM observation of the cast material and processed material of Comparative Example 1. It can be seen that the hexagonal intermetallic compounds observed in these figures have a small aspect ratio and therefore do not break even when strain is applied (see the arrows in the figures). Also, FIG. 9 shows the results of EPMA analysis of this hexagonal intermetallic compound, which indicates that this hexagonal intermetallic compound is an intermetallic compound composed of Mg, Al, Cu, and Mn. This is also true for Comparative Example 2. Such intermetallic compounds are slightly observed in Comparative Examples 6 and 10, but are not observed in the other Examples and Comparative Examples. This indicates that the addition of Mn is a factor in the generation of coarse intermetallic compounds.
[0045] 10 and 11 are composition images obtained by SEM observation of the cast material and processed material of Comparative Example 3, in which the Cu content exceeds 13.0 mass%. Coarse block-shaped intermetallic compounds are observed, and since these coarse intermetallic compounds have a small aspect ratio, they are not broken even when strain is applied. This is also the case in Comparative Example 4, and is slightly observed in Comparative Example 7. This indicates that when the Cu content exceeds 13.0 mass%, Cu is mainly consumed to generate coarse block-shaped intermetallic compounds with a small aspect ratio.
[0046] <Castability test> Each raw material was prepared and heated to 700°C, and poured into an iron mold capable of producing a rectangular parallelepiped casting with the composition shown in Table 2 and measuring 5 mm thick, 35 mm wide, and 235 mm long. The iron mold had an open long end and an air hole at the opposite end, and pouring was carried out from the open end. The length of the cast specimens obtained is shown in Table 2, and it was found that an Al content of 7.0 mass% or more is desirable to obtain sufficient castability.
[0047] [Table 2]
[0048] <Corrosion rate and mechanical property tests> The processed materials according to each of the examples and comparative examples were immersed in a 2% KCl aqueous solution (93°C), and the mass (mg) and surface area of the test specimens were measured before and after the test to determine the corrosion rate per day (mg / cm 2 / day:mcd) was calculated. In addition, tensile tests were performed on these processed materials in accordance with JISZ2241 (ISO6892). These test results are shown in Table 3. Here, the surface of Comparative Example 5 was white after the corrosion test, whereas the surfaces of the other Examples and Comparative Examples were gray after the corrosion test. In addition, the corrosion rate of Comparative Example 5 was extremely low compared to the other Examples. This is thought to be because the Al content was too high, causing stable corrosion products to form and adhere. Therefore, it is desirable for the Al content to be 13.0% by mass or less.
[0049] From Table 1, Example 11, Example 13, and Comparative Example 10 have the same Al and Cu contents and the average equivalent diameter d of the intermetallic compounds, but the Mn contents are different, 0.032 mass%, 0.077 mass%, and 0.10 mass%, respectively. From Table 3, the corrosion rates of Example 11 and Example 13 are the same, 2616 mcd and 2797 mcd, but the corrosion rate of Comparative Example 10 is smaller, 2259 mcd. This shows that the corrosion rate decreases when the Mn content is 0.10 mass% or more.
[0050] As shown in FIG. 12, the corrosion rates of the processed materials of Examples 1 to 10 can be linearly arranged according to the above formula (1) using the Al content AL (mass%), the Cu content CU (mass%), and the parameter Pc represented by the average equivalent diameter d (μm) of the Cu-Al-Mg intermetallic compounds.
[0051] Pc=(CU 2 / AL 2 ) / (1+p×d) (1)
[0052] Here, p is a constant, and in this embodiment, p=0.38. The corrosion rate can be estimated based on the above formula (1) and formula (2), and the estimated corrosion rate:W Est = 1697 × Pc + 949 ... (5) Based on the estimated corrosion rate, it is possible to design a magnesium alloy with any corrosion rate.
[0053] From the above formula (1), it can be seen that the higher the Cu content, the higher the corrosion rate, and the higher the Al content, the lower the corrosion rate. In order to obtain sufficient melt flowability, it is preferable that the Al content is 7.0 mass% or more. In Example 2, in which the Al content is 7.38 mass% and the Cu content is 4.65 mass%, the corrosion rate is 1362mcd. Since this corrosion rate is equivalent to the general decomposition rate of 1000 to 1500mcd for a decomposable frack plug, it can be said that the Cu content is preferably 4.5 mass% or more in order to obtain a practical corrosion rate as a highly decomposable magnesium alloy. Note that data for comparative examples is also shown in FIG. 12, and the corrosion rate of the comparative example is at a lower level than the linear relationship obtained from the examples, which also shows that the corrosion rate was reduced due to the metal structure characteristics described above.
[0054] [Table 3]
[0055] Table 4 shows the corrosion rates in Table 3 calculated using the above formula (5) W Est In Examples 1 to 14, this value was 0.90 to 1.10, whereas in Comparative Examples 1 to 7, this value was 0.81 or less, which clearly shows that the corrosion rates in the Comparative Examples were at a lower level than the estimated corrosion rate obtained from the above formula (5).
[0056] [Table 4]
[0057] 13 is a graph showing the Mn content on the horizontal axis and the values in Table 4 on the vertical axis for the processed materials of Examples 1 to 14 and Comparative Examples 1, 2, 6, and 10. It can be seen that in the comparative examples where the Mn content is 0.10 mass% or more, the corrosion rate is at a lower level than the estimated corrosion rate obtained from the above formula (5).
[0058] 14 is a graph showing the Cu content on the horizontal axis and the values in Table 4 on the vertical axis for the processed materials of Examples 1 to 14 and Comparative Examples 3, 4, and 7. It can be seen that in the comparative examples in which the Cu content exceeds 13.0 mass%, the corrosion rate is at a lower level than the estimated corrosion rate obtained from the above formula (5).
[0059] Furthermore, as shown in FIG. 15, the tensile strengths of the processed materials of Examples 1 to 14 can be linearly arranged according to the above formula (3) with the Al content AL (mass%), the Cu content CU (mass%), and the parameter Ps represented by the average equivalent diameter d (μm) of the Cu-Al-Mg intermetallic compounds.
[0060] Ps = u × AL-CU + v / (d) 1 / 2 (3)
[0061] Here, u and v are constants, and in this embodiment, u = 3 and v = 40. From this linear relationship, the tensile strength can be estimated based on the above formula (4), and the estimated ultimate tensile strength: σ T,Est [MPa] = 2.577 × Ps + 185……(6) Based on the estimated tensile strength, it is possible to design magnesium alloys of any desired strength.
[0062] From the above formulas (1) and (3), it can be seen that the corrosion rate and the tensile strength are not necessarily contradictory. Therefore, in the composition ranges of 7.0≦Al≦13.0, 4.5≦Cu≦13.0, and 0≦Mn<0.10 in mass%, the corrosion rate and tensile strength of decomposable structural components manufactured from magnesium alloys can be individually controlled by adjusting the Al content, the Cu content, and the average equivalent diameter of the Cu-Al-Mg intermetallic compounds based on the relationship between these parameters Pc and Ps and the corrosion rate and the tensile strength.
[0063] For example, when the average equivalent diameter d of the intermetallic compounds can be controlled to 0.5 μm or more and less than 2 μm according to the above formulas (1) and (5), it is preferable to adjust the Cu content to a range of more than 12.0 mass% and less than 13.0 mass% in order to adjust the corrosion rate to 1500 mcd or more. Also, when the average equivalent diameter d can only be 2 μm or more and less than 4 μm due to manufacturing reasons or restrictions due to the shape of the member, it is preferable to adjust the Al content to 10.0 mass% or more and less than 11.0 mass% and the Cu content to more than 10.0 mass% and less than 13.0 mass% in order to adjust the corrosion rate to 1500 mcd or more. In addition, when the average equivalent diameter d can be controlled to 0.8 μm or more and 1.2 μm or less, in order to design a decomposable magnesium alloy or member having a tensile strength of 300 MPa or more and a corrosion rate of 2000 mcd or more and less than 5500 mcd, it is preferable to prepare the chemical composition so that the Al content is 7.0 mass% or more and 13.0 mass% or less, and the Cu content is 12.5 mass% or more and 13.0 mass% or less, based on the above formulas (1), (3), (5), and (6). In particular, in order to design a decomposable magnesium alloy or member having a tensile strength of 305 MPa or more and a corrosion rate of 2500 mcd or more and less than 5000 mcd, it is preferable to prepare the chemical composition so that the Al content is 7.7 mass% or more and 10.8 mass% or less, and the Cu content is 12.5 mass% or more and 13.0 mass% or less. Similarly, when the average equivalent diameter d can be controlled to 0.8 μm or more and 1.2 μm or less, in order to design a decomposable magnesium alloy or component having a tensile strength of 315 MPa or more and a target corrosion rate in the range of 1500 mcd or more and less than 4000 mcd, it is preferable to prepare the chemical composition so that the Al content is in the range of 9.0 mass% or more and 13.0 mass% or less, and the Cu content is in the range of 9.0 mass% or more and 13.0 mass% or less.
Claims
1. A magnesium alloy comprising 7.0 mass% or more and 13.0 mass% or less of Al, 4.5 mass% or more and 13.0 mass% or less of Cu, 0 mass% or more and less than 0.10 mass% of Mn, with the remainder being Mg and unavoidable impurities, and the average equivalent diameter d of dispersed intermetallic compounds being 10 μm or less.
2. A decomposable structural member made of the magnesium alloy according to claim 1.
3. A method for producing a decomposable structural member, comprising the steps of: casting a magnesium alloy having the composition ratio recited in claim 1; and then processing the alloy to refine and disperse Cu-Al-Mg intermetallic compounds.
4. A method for adjusting either or both of the decomposition rate and the mechanical properties by adjusting the size and distribution of the Cu-Al-Mg intermetallic compounds in a magnesium alloy having the composition ratio set forth in claim 1 or in a decomposable structural member set forth in claim 2.
Citation Information
Patent Citations
Rapid-corrosion magnesium alloy product and preparation method thereof
CN104498792A
Na-contained rapid degradation magnesium alloy and preparation method thereof
CN107523732A
High-strength rapid-decomposition magnesium alloy for oil exploitation tripping ball and preparation method
CN107587019A
Highly corrosive magnesium alloy
JP1990232332A
Heat resistant magnesium alloy
JP2005054233A